Cobblestone appearances in dermatology - Anup Kumar Tiwary; Piyush Kumar (Wolters Kluwer Medknow Publications, 2021)
Dermatology is a visual medical discipline which demands watchful eyes, profound knowledge of different morphologic patterns of various dermatoses, and extensive clinical experience. A meticulous cutaneous examination always helps in generating the close differential diagnoses and incorporation of past visualexperience leads to a provisional diagnosis, obviating the need of further investigations in many cases. Although there is a wide spectrum of morphologic presentations, some dermatoses may have characteristic appearances such as cobblestoning, Peau d' orange, umbilication, and Christmas-tree pattern. Identification of these lesional characteristics or patterns can efficiently avoid the misdiagnosis and unnecessary diagnostic workup. In this article, skin diseases showing cobblestone appearances on both clinical and dermoscopic examination have been compiled and outlined in brief.